Compliance with adjuvant treatment guidelines in endometrial cancer: room for improvement in high risk patients - Eggink, F.A.; Mom, C.H.; Boll, D.; Ezendam, N.P.M.; Kruitwagen, R.F.P.M.; Pijnenborg, J.M.A.; van der Aa, M.A.; Nijman, H.W. (Gynecologic oncology, 2017)
Compliance of physicians with guidelines has emerged as an important indicator for quality of care. We evaluated compliance of physicians with adjuvant therapy guidelines for endometrial cancer patients in the Netherlands in a population-based cohort over a period of 10years. Data from all patients diagnosed with endometrial cancer between 2005 and 2014, without residual tumor after surgical treatment, were extracted from the Netherlands Cancer Registry (N=14,564). FIGO stage, grade, tumor type and age were used to stratify patients into risk groups. Possible changes in compliance over time and impact of compliance on survival were assessed. Patients were stratified into low/low-intermediate (52%), high-intermediate (21%) and high (20%) risk groups. Overall compliance with adjuvant therapy guidelines was 85%. Compliance was highest in patients with low/low-intermediate risk (98%, no adjuvant therapy indicated). The lowest compliance was determined in patients with high risk (61%, external beam radiotherapy with/without chemotherapy indicated). Within this group compliance decreased from 64% in 2005–2009 to 57% in 2010–2014. In high risk patients with FIGO stage III serous disease compliance was 55% (chemotherapy with/without radiotherapy indicated) and increased from 41% in 2005–2009 to 66% in 2010–2014. While compliance of physicians with adjuvant therapy guidelines is excellent in patients with low and low-intermediate risk, there is room for improvement in high risk endometrial cancer patients. Eagerly awaited results of ongoing randomized clinical trials may provide more definitive guidance regarding adjuvant therapy for high risk endometrial cancer patients. •Optimal adjuvant therapy for endometrial cancer is subject of debate.•In low and low-intermediate risk patients compliance to guidelines was 98%.•In high risk patients compliance to guidelines was 61%.•Results of ongoing clinical trials in high risk patients are eagerly awaited.